2014
DOI: 10.1111/eip.12133
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical characteristics of young people seeking help at youth mental health services: baseline findings of the Transitions Study

Abstract: The Transitions Study recruited a heterogeneous cohort at baseline in relation to the nature and severity of mental health problems and levels of functional impairment. The variation in clinical presentations within the cohort, from mild, through moderate to severe levels of psychopathology and impairment, increases the likelihood of the Transitions Study ultimately being able to achieve its aims of empirically testing a clinical staging model for mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 41 publications
3
57
4
Order By: Relevance
“…Finally, although we did report factor loadings for depressive symptom severity, we did not report on all conventional diagnostic criteria such as psychotic or manic symptoms collected in the Transition Study. Although these measures were found to be highly skewed in the sample, as can be expected, and therefore unlikely to impact our results (Purcell et al, 2015), future studies may benefit from an investigation of factor loadings of other diagnostic measures.…”
Section: Discussionmentioning
confidence: 54%
“…Finally, although we did report factor loadings for depressive symptom severity, we did not report on all conventional diagnostic criteria such as psychotic or manic symptoms collected in the Transition Study. Although these measures were found to be highly skewed in the sample, as can be expected, and therefore unlikely to impact our results (Purcell et al, 2015), future studies may benefit from an investigation of factor loadings of other diagnostic measures.…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, with broad spectrum youth mental health care primary care platforms, such as headspace, we now know that a much higher number of such young people can be engaged. In a recent study, we found that 38% of young people accessing these services reported attenuated psychotic symptoms likely to be in the UHR range.…”
Section: Solving the Prevention Paradox: Unlocking The Secret To Pre‐mentioning
confidence: 99%
“…This is a key strength of the model as it is able to effectively manage a high volume of cases through its broad-based entry, which is not possible through narrow approaches such as UHR clinics and traditional child and adolescent mental health services 22. The number of headspace clients with subthreshold psychotic symptoms ranges from 23% (based on preliminary findings from a large trial of UHR cases)23 to 38% 24. It is likely that not all of these cases would meet the full UHR criteria, however, access to care is clearly enhanced for earlier stage cases.…”
Section: Transition and Its Limitationsmentioning
confidence: 99%